Вы находитесь на странице: 1из 12

( )

, , 2012/13 .
..

I.
1. .
a. .
b. .
2. .
a. 1- 2-.
b. (n 1)-.
3. .
a. , .
b. .
c. , .
II. grad, rot, div
0. grad, rot, div.
1. .
a. 1-.
b. .
c. .
2. .
a. (n 1)-.
b. .
c. .
3. .
a. A B = rot A.
b. A B = rot A.
c. .


. ", ":
U (x, y, z)
(
)
U U U
grad U :=
,
,
.
x y z
A = (P, Q, R)(x, y, z)
(
)
R Q P
R Q P
rot A :=

.
y
z
z
x
x
y
B = (P, Q, R)(x, y, z)

P
Q R
div B :=
+
+
.
x
y
z
, , ,
, , . ,
- .

I.
1. .
a. .
, . , , n-
. 1 , ..., n , ( , )
. , .
x = xi i , y = y j j , x, y = xi i , y j j = i , j xi y j = gij xi y j . ,
, . , i , j = gij
.
, , gij = 0 i = j. , .

b. .
, , , ( ).
,
(gij ) . , x = xi i , x, y 0 y, i , j xi
= 0 gij xi = 0 j {1, ..., n}.
() , (gij )
.
2. .
a. 1- 2-.
2- , A 1- A, x. , , . , - a(x) = aj xj ( aj =
a(j )) A, x, A = Ai i ,
A a(j ) =
i , j Ai , j {1, ..., n}, , (gij ) .
, A = Ai i 1- a
{i }
aj = gij Ai

Ai = g ij aj .

b. (n 1)-.
, n-
B (n 1)- (B, ...).
A , B , , A1 = A, . Bn1 = n (B, ...), ,
n .

3. .
a. , .
n- () , - (t1 , ..., tn ) ( ) gij (t)dti dtj ,
, (t) t
( ) .
,
( ) , () .
, (n-) ,
n = det gij (t)dt1 ... dtn .
b. .
, (t1 , ..., tn )
, gij (t) 0 i = j.

ds2 = g11 (t)(dt1 )2 + ... + gnn (t)(dtn )2 ,

ds2 = E1 (t)(dt1 )2 + ... + En (t)(dtn )2 .
1 = (1, 0, ..., 0), ..., n = (0, ..., 0, 1) , t. () ,
, . , , i , i (t) = gii (t), .. |i | = gii (t),
i {1, ..., n}.
, (e1 , ..., en )( )
1
e1 = ( , 0, ..., 0) ,
g11

... , en = (0, ..., 0,

1
).
gnn

, ,
1
e1 = ( , 0, ..., 0) ,
E1

1
... , en = (0, ..., 0, ) .
En

c. , .
,
R3 .
. gij (t)dti dtj
(e1 , e2 , e3 ).
: (x, y, z), (r, , z) (R, , ) R3 gij (t)dti dtj
ds2 = dx2 + dy 2 + dz 2 =
= dr2 + r2 d2 + dz 2 =
= dR2 + R2 cos2 d2 + R2 d2 .
, :
ex = (1, 0, 0) ,
er = (1, 0, 0) ,
eR = (1, 0, 0) ,

ey = (0, 1, 0) ,
(
)
1
e = 0, , 0 ,
r
(
)
1
e = 0,
,0 ,
R cos

ez = (0, 0, 1) ;
ez = (0, 0, 1) ;
(
)
1
e = 0, 0,
.
R

II. grad, rot, div


0. grad, rot, div.
dU U 1-.
, , , 1- dU A, dU = A, ..
U grad U .
dU = grad U, ..

R3 (
) 1- A1 = A, .,
A. dA1 2-
B2 , , 3 , B (.. B2 = 3 (B, ., .)). B
A rot A.
2
, dA1 = rot
A.
n- (, Rn ) n , (n 1)- B, , Bn1 = n (B, ., .)). dBn1
(n1)- n-, , , n . B
div B.
, dBn1 = (div B) n .
1. .
a. 1-.
II, 2, a 1- A1 =
A, . A = Ai i . i

ei , , i = g ii ei ,
A = Aie ei {ei }
Aie = Ai g ii i {1, ..., n}.

Ai
aj = gij e
gii

Ai
e = g ij aj .
gii

A = Aie ei A1 = A, . = aj dtj , , 1-
1 = aj dtj A = Aie ei .
. , R3 1-
A1 = A, ., A = Aie ei .
: (x, y, z), (r, , z) (R, , ) R3 A1

A1 = Ax dx + Ay dy + Az dz =
= Ar dr + A r d + Az dz =
= AR dR + A R cos d + A R d.

b. .
A A1
dU = grad U, ., grad U =
U
U
U
j
i
ij
Aie ei . dU = t
gii t
j dt , .. aj = tj , Ae = g
j.
(gij ) , (g ij ),
g ii = 1/gii . ,
1 U
1 U
grad U =
e1 + ... +
en .
1
g11 t
gnn tn
c. , .
. grad U = Aie ei , R3 .
: (x, y, z), (r, , z) (R, , ) R3
grad U = Aie ei
U
U
U
ex +
ey +
ez =
x
y
z
U
1 U
U
=
er +
e +
ez =
r
r
z
U
1 U
1 U
=
eR +
e + 2
e .
R
R cos
R

grad U =

2. .
a. (n1)-.
, n- n- n , B
(n 1)- Bn1 = n (B, ...).
B =

B i i Bn1 = bi x1 ... xi ... xn , ,


{i } . ,
, xi ,

i , .. xi (v) := v i ; xi , ; n- n
n- x1 ... xn ,
(1 , ..., n ) .

, n = x1 ... xn
(v1 , ..., vn ) (vij ), , , , ,

n (B, ...) = ni=1 (1)i1 B i x1 ... xi ... xn .


Bn1 = n (B, ...), ,

n
n
1
i
n
i1 i 1
i
b
x

...

...

x
=
(1)
B
x

...

x
... xn .
i=1 i
i=1
, bi = (1)i1 B i i {1, ..., n}.
n c n = c x1 ... xn ,
, , bi = (1)i1 c B i
i {1, ..., n}.
, ,
{i }

1
det gij x ... xn , ,
,
gij = i , j .
, ,
() , , {i },

ei = i / gii . i = gii ei ,
B = B i i {i } B = Bei ei ,

Bei = gii B i .
,
, ng = det gij x1 ... xn

Bn1 = ng (B, ...), Bn1 = bi x1 ...xi ...


xn B B = Bei ei

ei = i / gii
bi = (1)i1

Bi
det gij e .
gii

det gij = g11 ... gnn .

i1

bi = (1)

g11 ... gii ... gnn Bei .

, ,
B(t)
Bn1 = ng (B, ...), .

, ng = det gij (t) dt1 ... dtn ,

Bn1 = bi (t) dt1 ... dti ... dtn ,

a B(t) = Bei (t) ei (t)


(t1 , ..., tn ),

det gij i
gii
i1
i
i1
bi = (1)
bi .
Be
Be = (1)

gii
det gij

,

bi = (1)i1 g11 ... gii ... gnn Bei .


, (t1 , t2 , t3 ), Ei = gii , B2 , B = Be1 e1 +Be2 e2 +Be3 e3

B2 = Be1 E2 E3 dt2 dt3 + Be2 E3 E1 dt3 dt1 + Be3 E1 E2 dt1 dt2 =


( 1
)

Be2
Be3
Be
2
3
3
1
1
2
= E1 E2 E3 dt dt + dt dt + dt dt
E1
E2
E3
( , 2- 2
b1 dt2 dt3 + b2 dt1 dt3 + b3 dt1 dt2 ,
a a1 dt2 dt3 + a2 dt3 dt1 + a3 dt1 dt2 , , P dy dz +
Qdz dx + Rdx dy.)
. , R3 2-
B2 = 3g (B, ...), B = Bei ei .
: (x, y, z), (r, , z) (R, , ) R3 B2

B2 = Bx dy dz + By dz dx + Bz dx dy =
= Br r d dz + B dz dr + Bz r dr d =
= BR R2 cos d d + B R d dR + B R cos dR d.
b. .
Bn1 = ng (B, ...) , , B ,
( n = 3),
() .
Bn1 n-, . ,
, B.
dBn1 = div B ng .
B = Bei ei
div B.

10

, B = Bei ei Bn1 . , , n-,


, B.
. (n 1)- Bn1

Bn1 = bi (t) dt1 ... dti ... dtn ,



)
(
n
bi
i1
dBn1 =
dt1 ... dtn ,
i=1 ti (1)
bi n1 Bei B =(Bei ei
(
))
n
det gij
n1
i

Be
dt1 ... dtn ,
dB =
i=1 ti
gii


ng = detgij (t) dt1 ... dtn ,

(
(
))
n
det gij
1
i

div B =
Be
.
i=1 ti
gii
det gij



(
(
))
g11 ...gnn
n
1

div B = g11 ...gnn


Be .
i=1 ti
gii
c. .
. B = Bei ei , R3 .
: (x, y, z), (r, , z) (R, , ) R3 div B B = Bei ei

Bx By Bz
+
+
=
x
y
z
(
)
1 rBr B
Bz
+
+
=
=
r
r

z
( 2
)
1
R cos BR RB R cos B
= 2
+
+
.
R cos
R

div B =

3. .
a. A B = rot A.

11

. , , , (t1 , t2 , t3 ) gij (t)dti dtj , , , 3g =

det gij (t) dt1 dt2 dt3 .


A = Aie ei 1 A1 , dA1 , 2- (
(n 1)-), B = Bei ei ,
, dA1 = B2 . B, , A rot A.
b. A B = rot A.
B = rot A
A.
A = Aie ei 1- A1 = A, .
g
A1 = ai dti = gijjj Aje dti ,

(
)
g
dA1 = tk gijjj Aje dtk dti =
( (
(
)
))
g
g
= t2 g3jjj Aje t3 g2jjj Aje
dt2 dt3 +
( (
)
(
))
g
g
+ t3 g1jjj Aje t1 g3jjj Aje
dt3 dt1 +
( (
(
)
))
g
g
+ t1 g2jjj Aje t2 g1jjj Aje
dt1 dt2 ,
B2 ,
B2 = dA1 =
b1 dt2 dt3 b2 dt3 dt1 + b3 dt1 dt2
g
Bei = ii bi B = rot A.
det(gij )


(t1 , t2 , t3 ) .
(
)
dA1 = (tk ( gii Aie )dtk dt( i =
))

= ( t2 ( g33 A3e) t3 ( g22 A2e)) dt2 dt3 +

+ ( t3 ( g11 A1e ) t1 ( g33 A3e )) dt3 dt1 +

+ t1
g22 A2e t2
g11 A1e dt1 dt2 ,

12

, Ei := gii
rot A = B = Be1 e1 + Be2 e2 + Be3 e3
)
( 3
1
Ae E3 A2e E2
1
Be =

,
t2
t3
E2 E3
)
( 1
3
1
A
E
A
1
e
e E3
Be2 =

,
3
t
t1
E3 E1
)
( 2
1
Ae E2 A1e E1
3
Be =

,
t1
t2
E1 E2

E1 e1
E2 e2
E3 e3

1

3
rot A =
1
2
E1 E2 E3 E A1 E A2 E A3
1 e
2 e
3 e

c. , .
. A = A1e e1 + A2e e2 + A3e e3 ,
R3 .
: (x, y, z), (r, , z) (R, , ) R3
rot A A = A1e e1 + A2e e2 + A3e e3
)
(
)
(
)
(
Ax Az
Ay Ax
Az Ay

ex +

ey +

ez =
rot A =
y
z
z
x
x
y
(
)
(
)
(
)
Ar Az
1 rA Ar
1 Az rA

er +

e +

ez =
=
r
z
z
r
r
r

(
)
(
)
1
A A cos
1 AR RA
=

eR +

e +
R cos

R
(
)
1 RA
1 AR

e .
+
R
R
cos